CAPACITY OF ADHYAKSA RESERVOIR IN NORTH JAKARTA - Trijeti Trijeti; Widha Wati Liestyowening (University Of Muhammadiyah Jakarta, 2021)
Adhyaksa reservoir is located within the Adhyaksa Public Hospital on Mabes Hankam street number 60, Ceger, Cipayung district, in the area of East Jakarta, which is one of the areas prone to flooding. Adhyaksa reservoir has a pump house available that is used to pump the excess water in the reservoir but there are still puddles in several places around the residential area. The problems occurs due to sedimentation in the canal, inadequate size of the canal, and narrowing of the canal. These causes the canal that is supposed to drain water into a reservoir to not work optimally. By conducting canal analysis using Log Pearson III method, using data obtained from 3 Rainfall Station namely, Bekasi Rainfall Station, Halim Rainfall Station, and Bogor Rainfall Station, it was found that the rainfall intensity that occured in the last 10 years cycle is 162,29 mm. Then, the Mononobe equation was used to find the intensity of rain per hour that occours. The planned rain discharge was then found using a rational method. From these calculations, it was discovered that there are 9 canals namely (5, 11, 12, 13, 17, 18, 19, 20 and 23) that are unable to accommodate the rainfall that occurs.